PEER CONFORMITY AND STUDENTS BULLYING BEHAVIOR AND IMPLICATIONS FOR GUIDANCE AND COUNSELING SERVICES - Sabilla Hasanah; Afrizal Sano (Universitas Negeri Padang, 2020)
This research is backgrounded by the phenomenon of bullying behavior that occurs in adolescents. Bullying behavior occurs because of the emergence of power mismatch between the perpetrator and the victim. Bullying behavior that occurs is related to the influence of peers. Youth bullying behavior is based on wanting to be recognized as a member of a peer group. The purpose of this study is to describe peer conformity and student bullying behavior. The method used is literature study. Bullying behavior can be prevented through the efforts of the Guidance and Counseling Teacher/ Counselor through various Guidance and Counseling services that aim to optimize student development.